SOUTH KOREA’S MUSLIM FRIENDLY TOURISM PROGRAM AS PUBLIC DIPLOMACY IN 2015-2019 - Nola Hilwa (Mediasi: Journal of International Relations, 2021)
The tourism industry is one of the influential industries in South Korea as effect of the spread of popularculture of South Korea to international society. South Korea's progress in tourism also impacts on Muslim tourists'interest to visit the country. Seeing this progress in tourism industries, South Korea try to take advantage of theseopportunities. One of the methods used by South Korea is by choosing public diplomacy in implementing MuslimFriendly Tourism (MFT) policies and obtaining assistance from non-governmental organizations in itsimplementation. This study uses a descriptive qualitative research method derived from the analysis of literature dataand scientific writings that have been collected, then described in a more detailed elaboration. This study is analyzedusing the Halal Tourism and Public Diplomacy concept in this research, the three dimensions of public diplomacybecome the focus of analysis, include: News Management, Strategic Communication, and Relationship Building.Public diplomacy efforts in implementing Muslim Friendly Tourism (MFT) carried out by South Korea from 2015 to2019 have contributed to the growth in South Korean Muslim tourists.